Genetically predicted circulating levels of cytokines and the risk of depression: a bidirectional Mendelian-randomization study - Wang, Meiti; Jin, Guixiang; Cheng, Ying; Guan, Shi-Yang; Zheng, Jinxin; Zhang, Shun-Xian (Frontiers in Genetics, 2023)
Objective: Inflammatory cytokines disturbance is the main result of immune dysregulation, which is widely described in major depressive disorder (MDD). However, the potential causal relationship between these two factors has not been discovered. Therefore, the purpose of this study was to investigate the causal relationship between inflammatory cytokines and MDD risk by using the two-sample Mendelian randomized (MR) analysis.Method: Two genetic instruments obtained from publicly available gene profile data were utilized for the analysis. We obtained the genetic variation data of 41 inflammatory cytokines from genome-wide association studies (GWAS) meta-analysis of 8293 individuals of Finnish descent. The MDD data, including 135,458 MDD cases and 344,901 controls, were obtained from the Psychiatric Genomics Consortium Database. For the Mendelian randomization (MR) estimation, several methods were employed, namely MR-Egger regression, inverse variance weighting (IVW), weighted median, and MR-Pleiotropy RESidual Sum and Outlier (MR-PRESSO) methods.Result: A causal relationship was identified between the genetically proxied levels of Interleukin(IL) -18, IL-1β, and Regulated upon activation normal T cell expressed and secreted (RANTES) and the risk of MDD (OR=0.968, 95%CI =0.938, 0.998, P =0.036; OR=0.875, 95%CI = 0.787, 0.971, P =0.012; OR=0.947, 95%CI =0.902, 0.995, P =0.03; respectively). However, our Mendelian randomization (MR) estimates provided no causality of MDD on inflammatory cytokines.Our study elucidates the connection between inflammatory cytokines and MDD by using MR analysis, thereby enhancing our comprehension of the potential mechanisms. By identifying these associations, our findings hold substantial implications for the development of more effective treatments aimed at improving patient outcomes. However, further investigation is required to fully comprehend the exact biological mechanisms involved.